Cost of Illness: Stroke Patients with Medical Rehabilitation - Santoso, Mahar; Adisasmito, Wiku BB; Hasibuan, Syarif Rahman (Jurnal Keterapian Fisik, 2024)
Background: Cerebrovascular disease (ICD 10: I60–I69), is a medical condition that leads to limitations such as limited mobility and cognitive impairment. It is the most fatal disease in Indonesia. Medical rehabilitation has been clinically proven to be an effective strategy to minimize disability in stroke patients. Methods: This research is a quantitative study with a cross-sectional design. The data source was obtained from BPJS Kesehatan sample data for 2022. The sample units for this study were all patients with a diagnosis of cerebrovascular disease. This study examined 3,528 patients, representative of a larger population of 339,707 patients. Results: In 2022, healthcare costs for stroke patients in Indonesia, covered by BPJS Kesehatan, varied widely from Rp 1,937,400 to Rp 207,675,700, averaging Rp 8,487,531 per person. BPJS Kesehatan's total spending on stroke treatment and rehab in 2022 was Rp 2,883,269,825,972. The productive age group constitutes the majority of stroke cases, comprising 68.9% of the total, with males representing the predominant gender at 54.5%. The biggest group benefiting from this were those receiving Beneficiary Contribution Assistance (PBI), making up 46.5% of all National Health Insurance participants. Conclusion: This study indicates that providing medical rehabilitation during the golden period yields greater efficiency compared to its absence. This recommendation extends beyond cost-saving measures, emphasizing a strategic investment in national welfare through the enhancement of individuals' quality of life. Therefore, policymakers, BPJS Kesehatan, hospitals, and healthcare professionals are encouraged to factor this insight into their decision-making processes.